Searching for FHB Resistances in Bread Wheat: Susceptibility at the Crossroad - Fabre, Francis; Rocher, Florian; Alouane, Tarek; Langin, Thierry; Bonhomme, Ludovic (Frontiers in Plant Science, 2020)
Fusarium head blight (FHB), primarily caused by Fusarium graminearum, is one of the most devastating fungal wheat diseases. During the past decades, many efforts have been deployed to dissect FHB resistance, investigating both the wheat responses to infection and more recently, the fungal determinants of pathogenicity. Although no total resistance has been identified so far, they demonstrated that some plant functions and the expression of specific genes are needed to promote FHB. Associated with the increasing list of F. graminearum effectors able to divert plant molecular processes, this fact strongly argues for a functional link between susceptibility-related factors and the fate of this disease in wheat. In this review, we gather the more recent data concerning the involvement of plant and fungal genes, functions and mechanisms in the development of FHB susceptibility, and we discuss the possibility to use them to diversify the current sources of FHB resistance.